32-Channel silicon strip detection module for combined X-ray fluorescence spectroscopy and X-ray diffractometry analysis - Carminati, Marco; Borghi, Giacomo; Demenev, Evgeny; Gugiatti, Matteo; Pepponi, Giancarlo; Crivellari, Michele; Ficorella, Francesco; Ronchin, Sabina; Zorzi, Nicola; Borovin, Evgeny; Lutterotti, Luca; Fiorini, Carlo (Frontiers in Physics, 2022)
A compact detection module for the simultaneous measurement of XRF and XRD in portable analytical applications, in particular in the mining sector, is presented. The detector head is based on 32 silicon strip detectors, fabricated with a low-leakage technology by FBK and readout by two 16-channel low-noise CUBE charge-sensitive amplifiers. The design of the module and its characterization are reported. Multiple configurations are experimentally compared in terms of strip length, spacing, collimation and charge sharing effects. The optimal configuration for a strip length of 6mm and pitch 0.2mm is thus identified. It offers an energy resolution of better than 200eV at 5.9keV with moderate cooling (-10°C) and peaking time of 14us.